2003
DOI: 10.1614/0890-037x(2003)017[0330:rsptim]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Relating Simazine Performance to Irrigation Management1

Abstract: Although water is crucial to the performance of preemergence herbicides, pesticide performance has rarely been related to irrigation management. This 2-yr study investigated the effect that amount of irrigation water applied had on activity of simazine. Three rates of simazine at 0, 1.12, and 2.24 kg/ha were applied to a 3-yr-old nectarine orchard that was irrigated with microsprinklers. The performance of simazine was compared between irrigation treatments initially targeted to provide water at 110 (efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Relatively few studies have directly examined the effects of altered irrigation on herbicide persistence and carryover in the soil. DaSilva et al (2003) reported better performance and reduced dissipation of simazine in an efficiently irrigated orchard compared to an overwatered one. Shaner and Wiles (2009) also worked with atrazine in a variety of deficit irrigation cropping systems but observed that prior use and preconditioning were more important in determining dissipation than water.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few studies have directly examined the effects of altered irrigation on herbicide persistence and carryover in the soil. DaSilva et al (2003) reported better performance and reduced dissipation of simazine in an efficiently irrigated orchard compared to an overwatered one. Shaner and Wiles (2009) also worked with atrazine in a variety of deficit irrigation cropping systems but observed that prior use and preconditioning were more important in determining dissipation than water.…”
Section: Introductionmentioning
confidence: 99%